2021
DOI: 10.3390/pharmaceutics13030380
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as Therapeutic Tools and Biomarkers for Prostate Cancer

Abstract: Prostate cancer (PCa) is the fifth cause of tumor-related deaths in man worldwide. Despite the considerable improvement in the clinical management of PCa, several limitations emerged both in the screening for early diagnosis and in the medical treatment. The use of prostate-specific antigen (PSA)-based screening resulted in patients’ overtreatment and the standard therapy of patients suffering from locally advanced/metastatic tumors (e.g., radical prostatectomy, radiotherapy, and androgen deprivation therapy) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 187 publications
(209 reference statements)
0
16
0
1
Order By: Relevance
“…LncRNA, a type of ncRNA with a transcript longer than 200 nt, does not encode proteins or only encodes short peptides (14,15) A large number of studies have revealed that lncRNA plays a non-negligible role in the development of PCa (21,22). Prostate cancer antigen 3 (PCA3), as one of the LncRNAs, has been proven to be a diagnostic marker to improve the diagnostic efficacy of PSA in PCa and has been approved by the FDA to guide repeated prostate biopsy (23,24). The lncRNA sequence contains nucleic acid binding sites and can be folded to form higher-level structures with corresponding protein-binding sites, which interacts with DNA, RNA, and proteins to affect the regulation of body functions (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA, a type of ncRNA with a transcript longer than 200 nt, does not encode proteins or only encodes short peptides (14,15) A large number of studies have revealed that lncRNA plays a non-negligible role in the development of PCa (21,22). Prostate cancer antigen 3 (PCA3), as one of the LncRNAs, has been proven to be a diagnostic marker to improve the diagnostic efficacy of PSA in PCa and has been approved by the FDA to guide repeated prostate biopsy (23,24). The lncRNA sequence contains nucleic acid binding sites and can be folded to form higher-level structures with corresponding protein-binding sites, which interacts with DNA, RNA, and proteins to affect the regulation of body functions (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…A major constraint is related to the need for safe and efficient delivery systems able to guarantee an enhanced cell type-specific delivery. Different miRNA delivery systems have been proposed thus far, and some of them have demonstrated the ability to inhibit tumor growth in in vivo models of PCa [ 65 , 165 , 166 , 167 , 168 ]. Additional challenges in developing miRNA-based therapeutics are related to the need for a more detailed understanding of the functions exerted by specific miRNAs and the precise identification of their key targets relevant to PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miRNAs have been largely implicated in the regulation of several processes underlying the development of different types of cancer, including PCa [ 64 ]. Dozens of miRNAs have been reported as deregulated in PCa tissues and cells compared to normal prostate, and for many of them a functional role has been described [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several blood-derived exosome markers have been developed and show potential diagnostic value in Pca ( 5 , 9 ). Circulating miRNAs serve as diagnostic biomarkers in multiple types of cancers, including biliary tract cancer ( 10 ), colorectal cancer (CRC) ( 11 ), Pca ( 5 , 12 ), glioblastoma ( 13 ), prostate cancer ( 14 ), lung cancer ( 15 ), hepatocellular carcinoma ( 16 ), and other tumors ( 17 ). Unlike the multiple reports on circulating miRNAs, only a few studies have reported the diagnostic values of plasma- or serum-derived exosome miRNAs in Pca ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%